Tingkat pencemaran peternakan babi yang diberikan pakan fermentasi Studi kasus kelompok mandiri Flamboyan terpadu Manokwari - Nugroho, Putra; Supriyantono, Andoyo; Pakage, Stefanus (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT : With the limited location and space available for livestock land and to prevent social conflicts that arise in society, due to the impact of environmental pollution from livestock activities, methods or methods are needed to reduce the impact of environmental pollution due to livestock activities, one of which is by modifying feed rations by fermentation method as carried out by the Manokwari Integrated Flamboyan Group. Based on this, it is necessary to measure the level of environmental pollution from pig farms that use fermented feed and to determine the levels of ammonia and methane produced. Measurement of public perception was carried out using a Likert scale and measurement of estimates of ammonia gas and methane produced using estimates based on the production of livestock manure produced. The overall perception of respondents for pig breeders who use fermented feed, all respondents stated that they were not very disturbed, while pig breeders who did not use fermented feed stated that they were quite disturbed. The results of statistical tests show that there is no difference in the estimates of ammonia and methane gas produced by pig breeders who use fermented feed and pig breeders who do not use fermented feed. This shows that the public's perception of pig farmers who do not use fermented feed is quite disturbed due to rations given.